Beautiful Majorana Higgses at colliders - Benjamin Fuks; Jonathan Kriewald; Miha Nemevšek; Fabrizio Nesti (Journal of High Energy Physics, 2025)
Abstract We investigate a novel collider signature within the minimal Left-Right Symmetric Model, featuring a Higgs sector composed of a bi-doublet and two triplets. Our study focuses on a region of the parameter space where the SU(2) R charged gauge boson W R lies in the multi-TeV regime (3–100 TeV) and the additional Higgs states play a significant role. In this scenario, a heavy neutral Higgs boson ∆ with a dominant SU(2) R triplet component can be produced in association with either a Standard Model Higgs boson or a massive weak boson. The subsequent decay of the heavy Higgs into Majorana neutrinos N results in displaced lepton signatures, providing a striking manifestation of lepton number violation. Additionally, we explore how the production of b-jets in these processes can enhance hadron-collider sensitivity to such signals. A particularly compelling channel, pp → b b ¯ NN $$ pp→ b\overline{b} NN $$ , offers the exciting possibility of simultaneously probing the spontaneous mass origin of both Dirac fermions and Majorana states. Based on an optimised event selection strategy and state-of-the-art Monte Carlo simulations, we outline the expected reach at the HL-LHC and future colliders. Our findings demonstrate that this channel probes a region of parameter space where the neutral Higgs triplet and heavy neutrino masses are relatively light (m ∆ ≲ 250 GeV, m N ≲ 80 GeV), indirectly constraining the W R boson to the deep multi-TeV domain, with sensitivity extending up to 70–80 TeV, effectively turning the LHC into a precision machine.